Chapter Marine protected areas and the problem of paper parks - Dorigatti, Josip (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Paper aim is to overview paper parks problem regarding Marine Protected Areas (MPAs). Ocean makes Earth habitable for humankind; careful management of ocean is a key feature of sustainable future. MPAs are a key instrument of ocean protection; MPAs effective management is essential to reduce environmental challenges. A 2017 WWF report highlighted that EU protected areas were at risk due to lack of proper implementation of EU laws by member states and the Commission legal actions. The Report showed the importance of both management plans and to involve all stakeholders in its developing process